All optical memory - Maizon Abdul Salim (School of Microelectronic Engineering, University Malaysia Perlis, 2011)
This project describes about all-optical memory comprises of three optical inputs with one modulated data signal at the transmission circuit and supports by another two control pulses circuits. These three inputs injected into two nonlinear optical switching loops (NOLS) which give the nonlinear effects towards the inserted inputs. The two NOLSs are connected with a connection line consists of erbium doped fiber amplifier (EDFA) and attenuator which supports the wavelength conversion process between the two NOSLs. This configuration of memory circuit is simulated using software called Optisystem. The obtained results have proven that, this all optical memory able to store data pattern and perform wavelength conversion. Finally, with this memory circuit, characteristic of some components inside this memory circuit such as power distribution, effects of SOA current injection and setting of time delay are explored through detailed analysis.